IDENTIFIKASI DAN ANALISIS HUBUNGAN PANJANG BOBOT IKAN GELODOK (FAMILI : GOBIIDAE) DI PANTAI BALI DESA MESJID LAMA KECAMATAN TALAWI KABUPATEN BATU BARA PROVINSI SUMATERA UTARA - Sabilah Fi Ramadhani; Yunasfi Djayus; Ahmad Muhtadi Rangkuti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Bali beach is one of the beaches in the Batu Bara, precisely located in the Mesjid Lama Village, Sub-district of Talawi, District of Batu Bara, North Sumatra Province. There is a coastal mangrove forests in this area. Mangrove is a good habitat for mudskipper. The research aims to determine identification and lenght weight analysis of mudskipper. The research was conducted from March until June 2014. The Method of the research is purposive sampling. For fishing example, the stations or area was used consisted of three transects of which are with beaches, mangroves, and rivers. There are four types of fish can be found in those areas, which are Periophthalmus chrysospilos, Periophthalmus gracilis, Boleophthalmus boddarti and Periophthalmonodon schlosseri. If we sorted that length weight relationship were 3.26 cm, 0.91 cm, 3.06 cm, and 3.01 cm.Keywords: Bali Beach, identification, length weight relationship, Mudskipper.